2015
DOI: 10.1093/jxb/erv468
|View full text |Cite
|
Sign up to set email alerts
|

Stability of small ubiquitin-like modifier (SUMO) proteases OVERLY TOLERANT TO SALT1 and -2 modulates salicylic acid signalling and SUMO1/2 conjugation inArabidopsis thaliana

Abstract: Small ubiquitin-like modifier proteases 1 and 2 (SUMO1/2) have been linked to the regulation of salicylic acid (SA)-mediated defence signalling in Arabidopsis thaliana. In order to define the role of the SUMO proteases OVERLY TOLERANT TO SALT1 and -2 (OTS1/2) in defence and to provide insight into SUMO1/2-mediated regulation of SA signalling, we examined the status of SA-mediated defences in ots1/2 mutants. The ots1 ots2 double mutant displayed enhanced resistance to virulent Pseudomonas syringae and higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 52 publications
2
58
1
Order By: Relevance
“…Here, not only did ulp1c/d display stomatal aperture defects, but we also confirmed that QQS was amongst the most up-regulated genes in this mutant. Moreover, ULP1c/d were recently implicated in the modulation of SA biosynthesis and signalling (Bailey et al 2016), further supporting the hypothesis that modulation of stomatal responses by ULP1c/d may involve SA.…”
Section: Ulp1c/d Are Implicated In the Control Of Developmentsupporting
confidence: 67%
“…Here, not only did ulp1c/d display stomatal aperture defects, but we also confirmed that QQS was amongst the most up-regulated genes in this mutant. Moreover, ULP1c/d were recently implicated in the modulation of SA biosynthesis and signalling (Bailey et al 2016), further supporting the hypothesis that modulation of stomatal responses by ULP1c/d may involve SA.…”
Section: Ulp1c/d Are Implicated In the Control Of Developmentsupporting
confidence: 67%
“…siz1 or sum1-1 amiR-SUM2) resulting in elevated SA, which promotes transition to flowering especially under short-days. Interestingly, SUMO1/2 or SUMO1/2(DGG) (conjugation-deficient SUMO mutants) overexpressing transgenic plants, or esd4 and ots1 ots2 mutant plants also accumulated higher level of SA and exhibited a severe earlyflowering phenotype under short-days, but a lesser extent under long-days (Murtas et al 2003;Conti et al 2008;van den Burg et al 2010;Bailey et al 2016). Similar to siz1, higher level of SA in esd4 is largely responsible for the early-flowering phenotype of esd4 under short-days (Villajuana-Bonequi et al 2014).…”
Section: Regulation Of Flowering Time By Sumo Conjugation/ Deconjugationmentioning
confidence: 99%
“…In addition to the phytopathogen-injected effector proteases that mediate deSUMOylation in order to alter plant defence responses, plant endogenous SUMO proteases are also known to play integral roles in the regulation of the defence responses (Bailey et al, 2016). Increased amounts of global SUMO conjugation in the ots1ots2 double mutant coincided with enhanced resistance to Pst DC3000 and elevated levels of SA relative to wild-type plants (Bailey et al, 2016). OTS1 and OTS2 limit SA biosynthesis by suppressing ISOCHORISMATE SYNTHASE1 (ICS1) expression.…”
Section: Sumo In Plant Defence Responsesmentioning
confidence: 99%
“…Similar to ubiquitination, the small ubiquitin-like modifier (SUMO), another potent post-translational protein modification system (Vierstra, 2012), is also capable of modulating target protein stability, interaction with partner proteins and subcellular localization (Wilkinson and Henley, 2010). Since its discovery in plants, SUMO has been associated with many different biological processes, such as growth, flowering, light signalling, abiotic stress responses and responses to pathogen infection (Bailey et al, 2016;Conti et al, 2008;Kurepa et al, 2003;Lee et al, 2007;Murtas et al, 2003;Sadanandom et al, 2015). Notably, one of the main classes of targets of SUMO modification is the transcription factors that coordinate transcriptional regulation during developmental and defence processes (Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%